PENGARUH PENGETAHUAN INVESTASI, LITERASI KEUANGAN, RISIKO INVESTASI DAN EFIKASI KEUANGAN TERHADAP MINAT INVESTASI MAHASISWA DI PMS - Waningsih, Reni; Meirini, Dianita (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Globalization has led to the emergence of a variety of investment products that are readily available to students for investing, particularly those enrolled in study programs in Islamic Financial Management and Islamic Economics who have taken courses on Islamic capital markets. In actuality, there is still not much enthusiasm in investing. This research was conducted to test the influence of investment knowledge, financial literacy, investment risk, and financial effectiveness on student investment interest in the Sharia capital market on students of Sharia Financial Management and Sharia Economy at UIN Sayyid Ali Rahmatullah Tulungagung. The method adopted for this study is a quantitative method. 245 students served as the main source of research data through the use of a questionnaire in data gathering. Data testing using SPSS 25 for validity tests, reliability tests, normality tests, multicolinearity tests and determination coefficient tests. Research results show that investment knowledge, financial literacy, financial effectiveness have a positive and significant impact on investment interest. Investment risk has a negative and significant impact on investment interest. Investment knowledge, financial literacy, investment risk, and financial effectiveness simultaneously have a positive and significant impact on student investment interest in the Sharia capital market